Financial Management "Jimpitan" - Hidayat, Narulita Alfiah Nurrizky; Prajawati, Maretha Ika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Cultures exist because of traditional ceremonies, inherited cultures, and social activities. Such as cultures carried out at research locations, by creating a new culture with social activities. This research was conducted to find out the origin, financial management, and benefits of the "Jimpitan" activity. Method research is qualitative. The research location is RT 1 RW 5 Kel. Pandanwangi. Data collection techniques using observation, interviews, and documentation. The number of informants used in this research was 7 informants. This research uses data analysis techniques, data reduction, and coding. The results of this research, the "Jimpitan" activity is still running for 1 year. This activity arose due to the construction of a camping post. Financial management by planning, organizing, implementing, and recording. The use of "Jimpitan" funds was made to support competition and carnival activities, for social activities, buying village facilities. The benefits of this activity are reducing existing fees and increasing RT's financial freedom.